2022
DOI: 10.3390/fermentation8070314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasound Application in Fermented Pineapple Peel on Total Phenolic Content and Antioxidant Activity

Abstract: Antioxidant phenolic compounds were extracted from fermented samples of Golden pineapple peels via an ultrasound method. The fermentation conditions to maximize the production of phenolic content and antioxidant activity were previously determined (pH: 5.5, T: 37.3 °C and 85% moisture content). A central composite design with 20 treatments was applied to evaluate the effect of the ethanol concentration, time, and temperature on the production of phenolic compounds and antioxidant activity of the extracts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
(78 reference statements)
2
8
0
Order By: Relevance
“…The results obtained are favorable according to Sepulveda et al [15] since they are within those already reported, reporting that DPPH values ranged from 27.4% ± 0.1 to 82.1% ± 1.4, while ABTS values ranged from 57.1 ± 0.2 to 95.0% ± 0.1, on the other hand, Polania et al [42] used pineapple waste fermented from Rhizopus oryzae to subsequently subject them to ultrasonic treatment, according to the results obtained from fermented extracts (61.46 ± 1.05 and 77.39% ± 1.18, DPPH and ABTS respectively) and combined fermentation with ultrasound (63.53% ± 2.02 and 80.06% ± 1.02, DPPH and ABTS respectively); they are similar to those obtained in the present study. On the other hand, Dulf et al [43], obtained methanol extracts of peach pomace from SSF using A. niger and R. oligosporus, although the antioxidant activity did not correlate with the bioactive compounds, positive results were obtained for inhibition by DPPH.…”
Section: Activity Antioxidantsupporting
confidence: 83%
“…The results obtained are favorable according to Sepulveda et al [15] since they are within those already reported, reporting that DPPH values ranged from 27.4% ± 0.1 to 82.1% ± 1.4, while ABTS values ranged from 57.1 ± 0.2 to 95.0% ± 0.1, on the other hand, Polania et al [42] used pineapple waste fermented from Rhizopus oryzae to subsequently subject them to ultrasonic treatment, according to the results obtained from fermented extracts (61.46 ± 1.05 and 77.39% ± 1.18, DPPH and ABTS respectively) and combined fermentation with ultrasound (63.53% ± 2.02 and 80.06% ± 1.02, DPPH and ABTS respectively); they are similar to those obtained in the present study. On the other hand, Dulf et al [43], obtained methanol extracts of peach pomace from SSF using A. niger and R. oligosporus, although the antioxidant activity did not correlate with the bioactive compounds, positive results were obtained for inhibition by DPPH.…”
Section: Activity Antioxidantsupporting
confidence: 83%
“…Caffeic acid -6.0 351 ASP39, GLY40, LEU41, LYS42, HIS45, ARG91, MET92, LEU98, LEU102, LEU134, ASN165, LEU166, ASN169, GLY170, SER171, SER172, GLY173, TYR266, GLN267, Hesperidin -8.3 351 ARG32, ALA33, PRO35, GLY40, LEU41, LYS42, VAL44, HIS45, SER83, ALA84, VAL85, ASP87, THR88, ARG91, MET92, LEU98, LEU102, ASN165, ASN169, GLY170, SER171, SER172, GLY173, ILE174, TYR266, GLN267 Ciprofloxacin -6.9 351 TYR86, ASP87, THR88, VAL90, ARG91, GLN94, PHE96, SER97, GLY110, SER111, ILE112, GLY114, ASP115, SER116, ALA117, TYR266, GLN267, VAL268 ARG92, GLN95, PHE97, SER98, TYR99, GLY111, SER112, MET113, GLY115, ASP116, ASN170, PRO219, THR220, ILE264, PRO265, PHE266, GLN267, VAL268, ASN269, LYS270 Caffeic acid -5.9 967 ARG92, GLN95, PHE97, SER98, SER112, MET113, ASP114, GLY115, THR220, ILE264, PRO265, PHE266, GLN267, VAL268, ASN269, LYS270 Hesperidin -10.1 967 GLY41, LEU42, LYS43, HIS46, GLU88, VAL91, ARG92, GLN95, PHE97, SER98, TYR99, PHE110, GLY111, SER112, MET113, ASP114, GLY115, ASP116, GLY117, ASN170, GLY171, ALA172, SER173, THR220, ILE264, PRO265, PHE266, GLN267, VAL268, ASN269, LYS270 Ciprofloxacin -8.0 967 LYS43, HIS46, ARG92, GLN95, PHE97, SER98, TYR9,9 SER112, MET113, ASP114, GLY115, SER173, THR220, PHE266, GLN267, VAL268, ASN269, LYS270 Journal of Food Processing and Preservation method demonstrated the presence of rosmarinic acid, caffeic acid, vanillic acid, ferulic acid, quercetin-3 glucoside, rutin, quercetin, kaempferol-3 gluco-side, and gallic acid, which demonstrates the great potential of these by-products to download components that are beneficial to the consumer's health [31]. Gallic acid, caffeic acid, p-coumaric acid, ferulic acid, are the major polyphenols quantified in papaya peel extracts [32].…”
Section: Discussionmentioning
confidence: 99%
“…Rosmarinic acid, caffeic acid, and hesperidin were used as ligands. These compounds were reported to be found in pineapple, papaya, and citrus, respectively [31][32][33]. The sdf files of the compounds were retrieved from PubChem using their respective CIDs: 5281792 for rosmarinic acid, 689043 for caffeic acid, and 10621 for hesperidin.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Another paper reported UAE combined again with preliminary solid-state fermentation (SSF) on some samples of Golden pineapple peels, using an ultrasonic bath at 35 kHz and varying the ethanol concentration, time and temperature [ 81 ]. Under optimal conditions (58% ethanol, 62 °C and 30 min), the extracts had a total phenolic content of 866.26 mg GAE/g and an activity (DPPH method) of 63.53 ± 2.02% [ 81 ]. UAE was also used in the study of Yahya et al, using 50% ethanol as the solvent at 30 °C [ 82 ].…”
Section: Alternative Methods For Green Extraction Of Bioactive Compou...mentioning
confidence: 99%